Analysis of Flexible Output Power Adjustment for Traction Substation inElectrified Railway - HAO Zuolin; XU Gencai; WU Liran; HU Liang (Kongzhi Yu Xinxi Jishu)
The catenary of electrified railway adopts single-phase single-side power supply mode, the power supply capacity of transformer winding supplying power to each power supply section is fixed, and it is difficult to support each other between power supply sections. This paper proposed a method to adjust output power of traction substation by balanced power supply technology. It connects adjacent power supply sections by high-power AC-DC-AC converter and reduces 20% to 40% of the peak value of impact load on each power supply arm. The proposed method realizes flexible output power adjustment in the traction substation, and ensures power supply capacity and security.